Deauville score versus ratio Deauville score in the interpretation of interim 18F-FDG PET-CT and in prediction of outcome in children with FDG-avid extra-nodal lymphomas - Hadeer Yousef Elhamady; Hosna Mohamed Mostafa; Huda Fathy Elsayed; Omnia Mohamed Abo-ElAzm; Mohamed Hany Hussein (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background Pediatric lymphoma is a common hematological neoplasm, representing the third most frequent childhood malignancy. 18F-fluoro-2-deoxyglucose–positron emission tomography has been found to be useful in lymphoma staging, prediction of prognosis and risk stratification of lymphoma patients. Although the interpretation of interim PET (after two cycles of chemotherapy) using the qualitative visual method of 5-point Deauville score has been widely accepted, semiquantitative methods of interpretation were evaluated by many studies and showed a better prediction of prognosis. The purpose of this study was to evaluate the prognostic role of the semiquantitative ratio Deauville score (rDS), defined as the ratio between target lesion and liver maximum standardized uptake values in children with FDG-avid extra-nodal lymphomas, undergoing interim FDG-PET/CT, and to compare it with the 5-point Deauville score (5p-DS). Methods This prospective study included 89 children with FDG-avid extra-nodal lymphoma. Interim PET was interpreted using both visual (5p-DS) and the semiquantitative method (rDS). The visual method depends on visual comparison of FDG uptake between lesions and liver as a reference organ for activity and considered lesions with activity higher than liver to be positive, while the semiquantitative method depends on making a ratio between the most active lesion and liver SUVmax. Receiver operating characteristic approach was applied to identify the optimal cut-point of rDS with respect to response to therapy and prognosis, and the prognostic significance of rDS was compared with 5p-DS. Results The ROC analysis for rDS as a predictor of progression showed an optimal cut-point of 1.25. Both 5p-DS and rDS were strong outcome predictors. Patients with negative 5p-DS and patients with rDS < 1.25 had a similar 3-year PFS (87%). Patients with a positive 5p-DS had a 3-year PFS of 67.4%, while patients with rDS > 1.25 had a 3-year PFS of 60%. Conclusions rDS could be suggested as an accurate prognostic factor in children with lymphoma undergoing interim FDG-PET/CT. However, larger studies with more homogenous sample regarding histopathological subtypes and chemotherapy lines are needed to confirm these data.